Cuckoo optimization algorithm for support vector regression potential analysis: An example from the Granites-Tanami Orogen, Australia - Roshanravan, Bijan; Kreuzer, Oliver P.; Mohammadi, Sadjad; Bruce, Matt; Davis, James; Briggs, Matt (Journal of geochemical exploration, 2021)
This study describes the supervised support vector regression method and cuckoo optimization algorithm (COA-SVR), a newly developed mineral potential modelling (MPM) technique, and a case study of its application to predicting gold potential in the Granites-Tanami Orogen (GTO), Australia. COA-SVR, which was borne out of a computer program coded in MATLAB®, incorporates a popular radial basis function (RBF) known as the Gaussian kernel function. The COA-SVR model was trained using a series of predictor maps previously generated and described by Roshanravan et al. (2020a), and corroborated by way of a 10-fold cross-validation. The modelling results indicate that the COA-SVR approach to MPM outperformed the previous data-driven (i.e., random forest) and continuous (i.e., fuzzy gamma, geometric average, and data-driven index overlay) models of Roshanravan et al. (2020a). As such, the newly proposed COA-SVR method presents a valid approach to MPM. To further constrain the results, the gold prospective domains identified via COA-SVR and the previous models of Roshanravan et al. (2020a) were delimited, using the student's t-value and concentration-area (C-A) fractal techniques. Following the above, indices of overall performance (Oe), accuracy (A), kappa (K) and normalized density (Nd) were applied to further assess the gold prospective domains as delimited by the student's t-value and C-A fractal techniques. The results are consistent with the COA-SVR and random forest models having outperformed the more traditional modelling approaches documented by Roshanravan et al. (2020a). Given the positive results obtained in this study and similarly positive results reported by others, we believe that the apparent superior nature of machine-learning algorithms strongly merits further consideration, research and more widespread application in MPM. [Display omitted] •New approach to mineral potential modelling called a COA-SVR•Approach was tested on orogenic gold systems in the GTO, Australia.•Results were compared to previously generated mineral potential models.•Results indicate that the COA-SVR method presents a valid approach to MPM.•Study highlighted there is a direct correlation between the indices of Oe, A and K.